The motivations of donor-conceived adults for seeking information about, and contact with, sperm donors. Issue 1 (July 2021) - Macmillan, Caitlin M.; Allan, Sonia; Johnstone, Melissa; Stokes, Mark A.
Highlights: The majority of donor-conceived adults had sought donor information (88%). The majority of donor-conceived adults had sought donor contact (71%). Common motivations reported for each: medical information, curiosity and identity. Logistic regressions found predictors varied between motivations and each act Abstract: Research question: How do the demographic characteristics, mental health experiences and disclosure experiences of donor-conceived adults shape motivations for seeking information about their sperm donors, contact with them, or both? Design: Sixty-nine Australian adults who conceived through sperm donors completed an online survey. Uniquely, information and contact seeking were investigated as two distinct concepts. Results: Participants reported a variety of demographic, mental health, disclosure and discovery experiences. Most had been motivated to seek information about their donor (88%), contact with them (71%), or both. The most commonly reported motivations for each act were for medical information, expanding their identity and curiosity. Logistic regression findings were significant for wanting medical information as a motivation for seeking donor information ( P  = 0.03). Endorsement of this motivation was associated with self-reported anxiety ( P  = 0.02) and less likely as participant age increased ( P  = 0.02). Motivation to contact donors for medical information was associated with self-reported anxiety ( P  = 0.02) and depression ( P  = 0.01), and more likely when the participant was raised in a household that included the recipient co-parent ( P  = 0.04). As years since disclosure or discovery increased, participants were less likely to report wanting medical information as a motivation ( P  = 0.02). Conclusion: Overall, participants were motivated to obtain information and seek contact with sperm donors. Motivations for each were similar despite participants varying in age and reporting a range of circumstances regarding disclosure, some of which were adverse.